Fuzzy Mamdani for the primary balloon shooter game - Fitra Nur Hanif (CEPAT Journal of Computer Engineering: Progress, Application and Technology, 2022)
Counting is a material that is considered not easy for most elementary school students. Not only from the considerations that are considered challenging but also the influence of the teacher's teaching style which makes bored, and boring is also a problem. In this study, an educational game balloon shooter prime numbers were made. In game design, the Mamdani fuzzy algorithm is applied to calculate the jumrance of balloons with the input variables of remaining_balloon and remaining_time. The application of the Mamdani fuzzy algorithm is considered successful, as evidenced by the high percentage rate of appearance of all balloons, reaching 76.4%.